2021
DOI: 10.1016/j.stemcr.2021.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic reactivity triggered by defective autophagy and metabolic failure causes neurotoxicity in frontotemporal dementia type 3

Abstract: Frontotemporal dementia type 3 (FTD3), caused by a point mutation in the charged multivesicular body protein 2B (CHMP2B), affects mitochondrial ultrastructure and the endolysosomal pathway in neurons. To dissect the astrocyte-specific impact of mutant CHMP2B expression, we generated astrocytes from human induced pluripotent stem cells (hiPSCs) and confirmed our findings in CHMP2B mutant mice. Our data provide mechanistic insights into how defective autophagy causes perturbed mitochondrial dynamics with impaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 64 publications
(74 reference statements)
0
15
0
Order By: Relevance
“…To evaluate the role of astrocytes in ALS, we differentiated hiPSCs from two ALS-patients with FUS mutations (R521H and P525L) and their corresponding CRISPR-Cas9 gene-edited isogenic controls (R521R and P525P) [ 25 , 27 , 28 ] into astrocytes using a slightly modified version of a recently published protocol [ 29 ]. The P525L mutation causes an aggressive juvenile form of ALS, while the more common R521H mutation causes adult-onset ALS [ 27 ], and the inclusion of both lines demonstrate a broad disease-onset spectrum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate the role of astrocytes in ALS, we differentiated hiPSCs from two ALS-patients with FUS mutations (R521H and P525L) and their corresponding CRISPR-Cas9 gene-edited isogenic controls (R521R and P525P) [ 25 , 27 , 28 ] into astrocytes using a slightly modified version of a recently published protocol [ 29 ]. The P525L mutation causes an aggressive juvenile form of ALS, while the more common R521H mutation causes adult-onset ALS [ 27 ], and the inclusion of both lines demonstrate a broad disease-onset spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…For the former group, a downregulation of HOTAIR (HOX transcript antisense RNA), STAT3 (signal transducer and activator of transcription 3) and Interferon signalling among others suggests a collective attempt to inhibit an immune response. Especially, HOTAIR regulates the NFκB-pathway [ 68 ], which is a major activator of the immune system response [ 69 ] and is involved in several neurodegenerative disorders [ 29 , 70 ] including ALS [ 71 , 72 ]. Notably, PI3K/AKT and BEX2 signalling, which were upregulated in R521H and P525L astrocytes, respectively, are also involved in NFκB-activation [ 73 77 ], and this dysregulation supports the heterogeneous reactive response observed in our astrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study on FTD3, it was shown that a point mutation in the CHMP2B (charged multivesicular body protein 2B), causes aberrant autophagy that in turn triggers perturbed mitochondrial dynamics with impaired glycolysis, increased ROS and elongated mitochondrial morphology, indicating increased mitochondrial fusion in FTD3 astrocytes. This alteration in astrocyte homeostasis prompts a reactive astrocyte phenotype and elevated release of toxic cytokines, which accumulate in NF-κB (nuclear factor kappa b) pathway activation leading to neurodegeneration [16] (Fig. 2).…”
Section: Astrocytic Mitochondria and Their Contribution In Neurodegen...mentioning
confidence: 99%
“…ICC, MitoTracker TM , WB, TEM and qPCR were performed according to previously described protocols (56). Image processing and analysis was performed in Fiji ImageJ 2.0.0-rc-65/1.51s.…”
Section: Microscopy and Qpcrmentioning
confidence: 99%